Kebijakan Pemerintah Tiongkok terhadap Konflik Uyghur dan Han: Studi Kasus Konflik Xinjiang di Tiongkok - Meancilla, Francisca; Pattipeilohy, Shary Charlotte Henriette (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The Xinjiang conflict is one of the internal conflicts that occurred in China. As a developed country, China is very vulnerable to conflict. This Xinjiang conflict is a conflict between ethnic Uyghurs and Han who later grew into a separatist movement. The ethnic Uyghurs escalated hostilities with the Chinese government and there were several separatist movements in Xinjiang that sparked the Chinese government's response. Meanwhile, the Chinese government will not release Xinjiang and will keep the territorial integrity. This study discusses to explain the main causes of the Xinjiang conflict and this conflict is still happening today. This study uses qualitative research methods, with the type of explanatory research because it is needed to explain why conflicts between Uyghurs and Han can occur. Using content analysis techniques that focus on Chinese government policies towards the Uyghur. By using the concept of Michael E. Brown about the causes of internal conflict. These causes are the underlying causes (Main Causes) and Proximate Causes (Additional Causes). Through this concept it was found that this conflict was not caused by just one factor which was released by four main factors relating to politics, economics, and culture. One of the reasons for this conflict is the Chinese state's interest in Xinjiang which is a potential region.